Fate, Eco-Toxicological Characteristics, and Treatment Processes Applied to Water Polluted with Glyphosate: A Critical Review - Villamar-Ayala, C (Taylor and Francis Inc., 2019)
Glyphosate is the most widely used active ingredient of Glyphosate Based Herbicides (GBHs), and which has environmental mobility towards water by its physicochemical characteristics. These properties determine its low availability in living organisms (log K ow < 0), which is increased by the presence of co-adjuvant activators in GBHs and its biodegradation (metabolites). Eco-toxicological studies have determined that glyphosate affects to several aquatic trophic-levels (freshwater/marine environments), being more toxics GBHs. Therefore, its potential environmental risk has promoted the development of conventional (biological and physicochemical) and non-conventional (Advanced-Oxidation-Processes or AOPs, combined processes) treatment strategies. Biological processes will generate incomplete degradation (metabolites generation), and variable removal efficiencies (25–99%). Physicochemical processes will be efficient (approx. 90%) but transferring the glyphosate from water to the adsorbent material (dangerous waste generation). Currently, AOPs will arise as a rapid (minutes) and effective alternative for glyphosate removal (>90%), depending on operational conditions, and without generation of intermediate metabolites. Moreover, new strategies (electrochemical) will avoid the hazardous waste production. Other combined processes (biological + physicochemical) will also reach glyphosate efficiencies removal above 90% but needing large spaces. However, their physical characteristics would make them feasible to be applied in agricultural areas. © 2019, © 2019 Taylor & Francis Group, LLC.